Impetus of E-Customer Satisfaction and Its Effects on E-Customer Loyalty: An SEM ‎Approach on App-Based Instant Home Delivery Services In an Emerging Market Context - Monirul Islam, S. M.; Kalam, Abul; Akter , Pinky; Islam , Md. Jahirul; Akterujjaman, S. M.; Ying Ying, Tiong; Idris Ali, Md. (International Journal of Accounting and Economics Studies, 2026)
Despite the widespread popularity of mobile apps for instant home delivery services, prior research has ‎largely overlooked a critical examination of the factors influencing the use of these apps, as well as ‎strategies to retain their customers. To address this gap, this study examines the key factors influencing the use of mobile apps for instant home delivery services and proposes strategies for customer retention by fostering customer loyalty. Drawing upon the SERVQUAL and Technology Acceptance Model (TAM) ‎frameworks, we identify techniques to enhance loyalty. Data for this study were collected from 605 users ‎of mobile apps for instant home delivery services through a questionnaire survey. The data were analyzed ‎using AMOS v. 24 and PROCESS Macro v. 4.20 software, employing SEM as well as PLS-Structural ‎Equation Modeling (PLS-SEM). Our findings reveal that the visual design of mobile apps, reliability, responsiveness, user-friendliness, and personal need fulfillment are the most significant predictors of app usage. ‎These factors drive e-customer satisfaction, which in turn enhances e-customer loyalty. Additionally, we ‎find the mediating role of e-customer satisfaction in the proposed relationships. We also investigate how ‎e-customer satisfaction can be turned into e-customer loyalty‎.